Effectiveness of Structured Intervention Module on Video Game Addiction among Adolescents in Nepal - Giree, Moushami; Das, Dorwin (Journal of Advanced Academic Research, 2024)
Introduction: Online gaming addiction has been associated with several detrimental effects in teenagers, such as worsening mental health, elevated levels of psychoticism, anxiety, and depression, strained family relationships, reduced quality of life, an increase in social anxiety, subpar academic performance, and enhanced sleep deprivation.Objective: This study aimed to assess the effectiveness of a structured intervention module on video game addiction among adolescents.Methods: A true experimental investigation was conducted among 348 adolescents from the control and 348 adolescents from the experimental group. The questionnaire was developed using the Gaming Addiction Scale. Data were coded, entered, and analysed using the Software Statistical Package for Social Sciences (SPSS) version 21. Data was analyzed using descriptive and inferential statistics (t-test).Results: The mean age of the participants in the control group and experimental group were 17.3, and 18.3 respectively. The majority of the participants were male in both the control and experimental groups (52.6% and 55.7%). About 39.7% of adolescents from the control group and 29.6% of the adolescents from the intervention group were studying in twelve standards. The majority of the participants in both the control and experimental groups started playing video games at the age of 7 to 8 years. The most popular mode of video game play among the participants in the control (61.5%) and experimental groups (60.3%), was online. Multi-player was highly preferred by study participants in both the control group (71.6%) and the experimental group (74.1%). After receiving interventions, video game addiction reduced significantly among the experimental group, from 42% to 25% during the post-test. However, the status of video game addiction remained constant among the control group at 46.3%. During post-tests, the study found that there was a significant difference in the mean scores between the control group (3.7±0.6) and the experimental group (1.9±0.7). The difference was found to be statistically significant (p